Teaching practices and pass rate in the subject of Numerical Methods of engineering common plan of the Metropolitan Technological University, year 2017 - Hidalgo Gallardo, Lorena Paola (2022)
The objective of this research was to determine the relationship between teaching practices and the passing rate in the subject Numerical Methods of the Common Engineering Plan of the Metropolitan Technological University, year 2017. The scope included the common plan of Engineering of the Faculty of Engineering, Macul headquarters, located at José Pedro Alessandri 1242, Macul. At the methodological level, it was a basic type research, descriptive level, non-experimental, correlational-causal transectional design, quantitative approach. The variables were broken down into dimensions, in the case of the teaching practice variable these were: methodology, evaluation and use of new technologies; for the approval rate variable, the dimension was performance. We worked with a sample of 119 students, the instruments were the survey, which made it possible to identify the existing teaching practices, and the report cards that made it possible to calculate the approval rate. Regarding the results, it was found that 47,06% believed that they received an acceptable teaching practice and 52,94% an excellent teaching practice, on the approval rate it could be established that it was 70.59%. Finally, it was concluded that teaching practice has a high positive relationship with the approval rate (Sig = 0.000; rs = 0.699). Regarding the relationship between the dimensions of teaching practice and the approval rate, a moderate positive relationship was concluded with methodology (Sig = 0.000; rs = 0.604) and evaluation (Sig = 0.000; rs = 0.509), a high positive relationship with the use of new technologies (Sig = 0.000; rs = 0.717).